Efeito-Audiência na Jornada Endossante Publicitário - Carmo, Alex Sandro de Araujo (2020)
The testimony of others about a given fact or event may be considered as the most used strategic resource along the history of advertising. Foreseeably, at a time when imperative advertising finds it difficult to sustain its effectiveness, the persuasive advertising message develops creative (non-subjective) discursive artifices with the use of celebrity endorsement to promote the sale of a specific product. From this perspective, also supported by the epistemology of Discourse Theory, the objective of this thesis aims at the effects of meaning reproduced by the practice of celebrity endorsement in advertising films that promote their own stimuli for the sale of overprocessed functional dairy foods. The theoretical bases of this work are based on the examination of the constitutive crossing of discursive practices that challenge the effects of meaning that determine the image of a healthy and beautiful body in the ideological promotional advertising practice and in the enunciation processes materialized in the narrative journey of the endorsed advertising film by celebrities. In other words, to study the selected corpus, different lines of research were used for conceptual support, such as French Discourse Analysis, especially in the postulates of Pêcheux (1993 [1969]), and Pêcheux and Fuchs (1993 [1975]) about the imaginary formations and the processes of enunciation, and the theories of Advertising Communication, especially those regarding the strategic issue of the advertising message. Thus, the conditions of production of advertising practice of advertising films with the use of endorsing strategies are understood to be subordinated to the imaginary, and the audience effect that supports (through celebrity staging) the lightness of the body as a disciplined and achieved result by actions developed from eating practices stated and announced as ideal and healthy.